FISIOLOGIS PERTUMBUHAN IKAN SELAIS (ompok hypophthalmus) PADA SISTEM RESIRKULASI AKUAKULTUR (SRA) - Nur Addini; Usman M Tang; Henni Syawal (Berkala Perikanan Terubuk, 2020)
The maintenance of selais with high density isn’t expected to affect the physiological condition of the growth of the leaf. Then an attempt to cultivate fish with RAS using biofilter in the form of mustard plants. The purpose of this study was to determine the effect of stocking density on water quality on RAS technology and to determine the effect of water quality on RAS technology on physiological and hematological fish species. The study was conducted on Oct 6th-Dec 6th 2019, at the Aquaculture Technology Laboratory, Riau University. Using an experimental method with a Completely Randomized Design, three treatments and three replications (200 fish/m3, 250 fish/m3, 300 fish/m3). Data obtained included total erythrocytes, hemoglobin levels, hematocrit levels, total leukocytes, absolute growth using one way ANOVA at a 95% confidence level analyzed with the SPSS 17.0 application program. if significantly different then proceed with the Student Newman Keuls test (P <0.05). Whereas water quality data are presented in tabular form and discussed descriptively. Physiologically the best growth density stocking 250 fish/m3, total final erythrocytes 264.00±3.00 x104 cells/mm3, final hemoglobin 8.3±0.11g/dL, final hematocrit 26.66±0.57%, final total leukocytes 2.53±0.01x104 cells/mm3, blood glucose 89.00±1.00 mg/dL, absolute weight growth 12.06±0.02g, absolute length 7.44±0.02cm, SGR 2.40±0.01%.